Test the Effectiveness of Carrot Tuber Ethanol Extract Cream Preparation Formulation in Preventing Increased Melanin in Male Wistar Rats Exposed to UVB Light - Wulan Dhari; Ali Napiah Nasution; Djohan; Widyaningsih Oentari; Widya Pasca Amir; Anita Merry Cisca; Ermi Girsang (Jurnal Multidisiplin Madani, 2023)
This study was conducted with the aim of proving carrot tuber extract (Daucus carota L.) formulated in cream form can prevent an increase in the amount of melanin in the skin tissue of male wistar rats (Rattus norvegicus) exposed to UVB light and see histopathological changes due to carrot tuber extract given as a prevention of increasing the amount of melanin. This study is experimental with a post-test only control group research design. The test method used was testing the amount of melanin modified using a 13 watt Exoterra UVB 200 lamp. The animals tested were rats (Rattus norvegicus) male wistar strain aged 2-3 months, weighing ± 200 grams. Male rats were randomly divided into 6 groups. Each group consists of 5 male rats. The test area on the back of the back is 2x2 cm2. Group I male rats without cream administration as a negative control group, Group II male rats for Parasol Face Sunscreen Cream as a positive group. Group III is the group with the provision of basic ingredient cream and group IV-VI is the group with the administration of 25% carrot tuber extract cream; 50 %; 75 %. topically for 4 weeks.. The evaluation was performed by observing the amount of melanin at week 4 of histopathology analyzing in the test area. The results will be processed with IBM SPSS 21.0 and analyzed with the steps of Descriptive Analysis, Normality Analysis with data using Shapiro-Wilk test and Homogeneity using Levene's test, Comparative Analysis using one way Anova test, followed by Post-hoc test with LSD test. If the data is abnormal, use non-parametric analysis of the Kruskal-Wallis test followed by the Mann-Whitney test. The results showed that extra ethanol of carrot tubers can prevent the increase in the amount of melanin. This was shown by its ability to reduce melanin and histopathological changes in a group of male rats applied carrot tuber ethanol extract cream within 4 weeks